Analysis of interaction of hydraulic fractures with natural fractures and bedding planes in layered formation through cohesive zone modelling. (February 2023) - Pidho, Justin Jordan; Liang, Yanbo; Cheng, Yuanfang; Yan, Chuanliang
Abstract: A model capturing micro-void nucleation with tensile and shear failure modes is developed to present interaction mechanism of propagating hydraulic fracture(s) (HF(s)) with shale bedding planes (BPs) and natural fracture(s) (NF(s)). The study objective is to translate algorithm for excess shear forces into understanding of NF and BP slip and dilation at junction of their intersection with HFs. The methodology is based on regularized global cohesive zone method (CZM) using viscous regularization implemented with Mohr- Coulomb frictional shear plasticity implemented through Newton-Raphson return mapping algorithm. The approach leverages understanding of multiple fracture geometries (width, length, height) when HF approaches NFs and BPs. In situ stress contrast shows more influence on creation of fracture complexity. Cluster spacing is shown to have moderate influence on shear opening at the intersection of HFs with BPS and NFs. Low dipping and weak shale beds demonstrated with dip angles of 30° and 45° and bed interfacial material strength of 1 MPa tend to propagate HFs along BPs. A 90 dip develops T -shaped fractures at weak interfacial strength. Comparison of field measured bottom-hole pressure (BHP) with simulated BHP in layered shale reservoir in the western Sichuan basin gives maximum error as low as 6 %. A measurement of junction dilation of 0.0055 m was recorded at highest injection rate 0.04 m 3 /s with an observation that the dilation progressively increased as stimulation time was prolonged. On contrary, lower injection rates of 0.003 m 3 /s, 0.01 m 3 /s and 0.02 m 3 /s recorded maximum dilation before the end of total stimulation time. Three-point bending test based on published experiment on shale play is used to test the performance of this model. Comparison with available solution in literature indicates superiority of the developed CZM vested in its removal of stress singularities at the fracture tips replacing it with the development of fracture process zone softening effect and micro-crack nucleation. This study is important in understanding field implementation of HFs in formations with NFs/BPs such as Longmaxi shale gas reservoir.